2023
DOI: 10.3390/s23136110
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning Algorithm to Monitor Upper Extremity Task Practice

Abstract: Upper extremity hemiplegia is a serious problem affecting the lives of many people post-stroke. Motor recovery requires high repetitions and quality of task-specific practice. Sufficient practice cannot be completed during therapy sessions, requiring patients to perform additional task practices at home on their own. Adherence to and quality of these home task practices are often limited, which is likely a factor reducing rehabilitation effectiveness post-stroke. However, home adherence is typically measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Specifically, a previous study found an F1 score of 0.84 when detecting compensatory movement during a simple task of arm raise in neurotypical adults and stroke survivors using the random forest [ 25 ]. Another study found an F1 score of 0.89 when detecting compensatory and incomplete movements during functional tasks in neurotypical adults using long short-term memory [ 26 ]. The present study found an F1 score of 0.95 in stroke survivors, possibly due to a person-specific modeling approach used compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, a previous study found an F1 score of 0.84 when detecting compensatory movement during a simple task of arm raise in neurotypical adults and stroke survivors using the random forest [ 25 ]. Another study found an F1 score of 0.89 when detecting compensatory and incomplete movements during functional tasks in neurotypical adults using long short-term memory [ 26 ]. The present study found an F1 score of 0.95 in stroke survivors, possibly due to a person-specific modeling approach used compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 functional tasks used in this study are described in Table 3 . More details of these tasks along with task instructions and pictures can be found in the study of Li et al, 2023 [ 26 ]. These tasks were chosen as representative functional tasks prescribed in home exercise programs from the task practice manual [ 32 ] and vary in difficulty.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of the monitoring devices should prioritize usability and patient comfort. Wearable motion sensors, such as IMUs or M-IMUs, offer a non-intrusive solution for continuous monitoring of shoulder movements during rehabilitation exercises [16,[25][26][27][28][29][30]32]. These devices are small, lightweight, non-invasive electronic devices, enabling real-time feedback and data collection, empowering patients to track their progress and adherence to prescribed exercises.…”
Section: Discussionmentioning
confidence: 99%